Studi Kebijakan Pendidikan di Kota Bogor dalam Perspektif Pendidikan Islam - Najamudin Najamudin; Surahman Hidayat (Universitas Maritim AMNI Semarang, 2023)
Education is one of the main pillars in human resource development, and effective education policies are essential to achieve this goal. This study aims to analyze education policies in Bogor City with an Islamic education approach, which emphasizes moral values, ethics, and character. The research method used is qualitative, with data collection techniques through documentation studies and in-depth interviews. Data were collected from various sources, including regional education policy documents, education evaluation reports, and interviews with education officials, educators, and local community leaders. The results of the study indicate that education policies in Bogor City have integrated several elements of Islamic education, such as an emphasis on noble morals, student character development, and the creation of a conducive learning environment. However, this study also identified several challenges in implementing the policy, including the lack of training for educators on the application of Islamic values in teaching, the uneven distribution of educational resources, and the lack of community participation in the education process. Further analysis revealed that existing education policies do not fully reflect the principles of holistic Islamic education, which should include spiritual, intellectual, and social aspects. This study recommends the need to strengthen the curriculum based on Islamic character education, increase training and professional development for educators, and increase collaboration between the government, schools, and the community in creating a more conducive educational environment. Thus, it is hoped that education policies in Bogor City can be more effective in forming a generation that is not only academically intelligent, but also has a deep understanding of Islamic values, is able to contribute positively to society, and becomes a role model in everyday behavior.